Comparison of pre- and intra-COVID-19 postpartum depression among reproductive aged women: A comparative cross-sectional study in Ahvaz, Iran - Afshari, Poorandokht; Tadayon, Mitra; Abedi, Parvin; Beheshtinasab, Maryam (Frontiers in Psychiatry, 2022)
Background: The association between PPD and COVID-19 pandemic has been studied in some countries. This study aimed to compare postpartum depression before and during the COVID-19 pandemic among reproductive-aged women in Ahvaz, Iran. Methods: This comparative cross-sectional study involved 600 women of reproductive age in Ahvaz, Iran during the COVID-19 pandemic who were compared with 504 of their counterparts before the pandemic. Literate women who had given birth 1-6 months prior to the study, were aged 18-35, and were willing to participate in this study were recruited. A demographic questionnaire and Edinburgh Postnatal Depression Scale were used to collect the data. Independent t-test, Chi-square, and Logistic regression were used to analyze the data. Results: Before the pandemic, only 123 (24.9%) of the women had PPD, while during the pandemic, this number rose to 409 (68.2%). During the COVID-19 pandemic, the women were 8.727 times more likely to have PPD (95% CI: 5.919-12.868). During the pandemic, women with high school education and those having a high school diploma were 2.454 and 2.054 times more likely to have PPD compared to women with a university degree (95% CI: 1.508-3.996 and 1.302-3.241, respectively). Conclusion: The prevalence of PPD among Iranian reproductive-aged women increased during the COVID-19 pandemic. Policymakers should seek some strategies to support women during pregnancy and postpartum in times of crises such as the COVID-19 pandemic.